FACILITATIVE SUPERVISOR: THE TRANSITION POINT OF SUPERVISOR DEVELOPMENT TO ACHIEVE PROFESSIONAL STANDARDS - Khobthong, Punyawat; Kornpuang, Anucha; Saengsawang, Phitthaya; Rattanasirinichakun, Nat (Journal of Education and Innovation, 2025)
This article aims to present the importance of supervisors as educational personnel who play an important role in driving education to achieve the goals of the national education plan. Presents the current concerns of supervisors that arise from teachers’ misunderstanding of the roles and responsibilities of supervisors, resulting in miscommunication problems between teachers and supervisors which are obstacles to reach teachers’ teaching management problems because it impossible to solve problems that arise directly. And also present the concept of developing the characteristics of supervisors that will help supervisors perform their duties to achieve professional standards by using various skills. To enable supervisors to access problems of teachers’ teaching management and lead to problem solving in the role of “facilitative supervisor”. Facilitative supervisor should have 6 skills are 1) Positive atmosphere creation skills, 2) Questioning skills, 3) Listening skills, 4) Powerful communication skills, 5) Exchange of thoughts and ideas skills, and 6) Reflective skills. The development of these skills will lead to the facilitator characteristics of new supervisors that will relate to and encourage the performance of duties according to the role of supervisors to achieve the supervisor professional standards.